The Threat of a Nuclear- Armed North Korea and the Possibility of Solutions - Zain Maulana (Universitas Muhammadiyah Yogyakarta, 2014)
This article tries to describe the threat of North Korea nuclear to regional and international security. North Korea Nuclear Proliferation is open the possibility of an arms race, even nuclear war in the region. Moreover, North Korea technology’s ability in produce nuclear weapon will improve the spread of the weapons, both towards other countries or foreign actors. It needs some regional policy innovation to prevent nuclear proliferation in the region.